2018
DOI: 10.21608/pssjn.2018.33320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Program on Nurses' practice Regarding Care of Adult Patients with Endotracheal Tube

Abstract: The majority of patients admitted to Intensive Care Unit (ICU) requiring endotracheal intubation to maintain oxygenation and ventilation. Aim: to study the effect of educational program on nurses' practices regarding care of adult patients with endotracheal tube. Methods: A quasi-experimental design was used on a convenience sample of all available nurses (50 nurses) who were working in Intensive Care Unit, Cardiac Care Unit and Cardiothoracic Care Unit at Suez Canal University Hospital. Two tools were develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…This confirms our finding in terms of enhancing nurses' knowledge. 13 Concerning the knowledge of mechanical ventilation (MV) aspect, the results of this study showed that most of the respondents (n=43, 49.4%) had inadequate knowledge at pre-test. While at the posttest, the majority of the nurses (n= 54, 62.1%) had an adequate knowledge as showed in table (2).…”
Section: Discussion Of the Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…This confirms our finding in terms of enhancing nurses' knowledge. 13 Concerning the knowledge of mechanical ventilation (MV) aspect, the results of this study showed that most of the respondents (n=43, 49.4%) had inadequate knowledge at pre-test. While at the posttest, the majority of the nurses (n= 54, 62.1%) had an adequate knowledge as showed in table (2).…”
Section: Discussion Of the Resultsmentioning
confidence: 85%
“…Additionally, this supports the findings of a previous research study conducted by Elsaman (2017) who found that improvement of participants' knowledge after providing endotracheal suctioning guidelines which reflected on patients' respiratory status. 12 Another study in Egypt that was carried by Hassan et al, (2018) aimed to determine the effect of educational program on nurses' knowledge regarding endotracheal tube of adult patients. The researchers declared that there were highly statistical significant differences between pre and post implementation of educational program regarding anatomy and physiology of respiratory system with the P<0.0001.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…The study revealed that there is no statistically significant correlation between nurses' years of experience in (CCU, RCU and medical and surgical wards) with their knowledge and practices toward indwelling catheter-associated with urinary tract Infections (at P ˃ 0.05) respectively. According to Hassan (2018), there is no significant association between nurses' educational levels and their practices (pvalue =0.07) (Hassa,2018). Chithra and Raju (2017) discovered a statistical association between nurses' expertise and their educational level (p-value =0.033) (Chithra and Raju,2017).…”
Section: Discussionmentioning
confidence: 99%
“…According to Hassan (2018), there is no significant association between nurses' educational levels and their practices (p-value =0.07) (Hassan, 2018). Chithra and Raju (2017) discovered a statistical association between nurses' expertise and their educational level (p-value =0.033) (Chithra and Raju., 2017).…”
Section: Discussionmentioning
confidence: 99%